New insights into the impact of microbiome on horizontal and vertical transmission of a tick-borne pathogen - Li-Feng Du; Ming-Zhu Zhang; Ting-Ting Yuan; Xue-Bing Ni; Wei Wei; Xiao-Ming Cui; Ning Wang; Tao Xiong; Jie Zhang; Yu-Sheng Pan; Dai-Yun Zhu; Liang-Jing Li; et al. (Microbiome, 2023)
Abstract Background The impact of host skin microbiome on horizontal transmission of tick-borne pathogens , and of pathogen associated transstadial and transovarial changes in tick microbiome are largely unknown, but are important to control increasingly emerging tick-borne diseases worldwide. Methods Focusing on a rickettsiosis pathogen, Rickettsia raoultii, we used R. raoultii-positive and R. raoultii-negative Dermacentor spp. tick colonies to study the involvement of skin microbiota in cutaneous infection with rickettsiae in laboratory mice, and the function of the tick microbiome on maintenance of rickettsiae through all tick developmental stages (eggs, larvae, nymphs, adults) over two generations. Results We observed changes in the skin bacteria community, such as Chlamydia, not only associated with rickettsial colonization but also with tick feeding on skin. The diversity of skin microbiome differed between paired tick-bitten and un-bitten sites. For vertical transmission, significant differences in the tick microbiota between pathogenic rickettsia-positive and -negative tick chorts was observed across all developmental stages at least over two generations, which appeared to be a common pattern not only for R. raoultii but also for another pathogenic species, Candidatus Rickettsia tarasevichiae. More importantly, bacterial differences were complemented by functional shifts primed for genetic information processing during blood feeding. Specifically, the differences in tick microbiome gene repertoire between pathogenic Rickettsia-positive and -negative progenies were enriched in pathways associated with metabolism and hormone signals during vertical transmission. Conclusions We demonstrate that host skin microbiome might be a new factor determining the transmission of rickettsial pathogens through ticks. While pathogenic rickettsiae infect vertebrate hosts during blood-feeding by the tick, they may also manipulate the maturation of the tick through changing the functional potential of its microbiota over the tick’s life stages. The findings here might spur the development of new-generation control methods for ticks and tick-borne pathogens. Video Abstract